Development of chromatographic methods to investigate the purification process of lactic acid from lactic acid bacteria - Petcharat Sura-apinan (Prince of Songkla University, 2012)
Thesis (M.Pharm., Pharmaceutical Sciences)--Prince of Songkla University, 2010